Leader Humility and Taking Charge: The Role of OBSE and Leader Prototypicality - Zhang, Wenwen; Liu, Wenxing (Frontiers in Psychology, 2019)
Taking charge refers to an extra role behavior that is change oriented and can bring constructive benefits to the organization. However, taking charge always involves risks and might incur potential costs for employees. Understanding how to encourage employees’ taking charge becomes increasingly important for today’s organizations. Drawing on self-concept-based theory, we intend to explore when and why leader humility would inspire followers’ taking charge behavior in China. Employing a time-lagged research design with a sample of 190 supervisor-subordinate dyads, we found that the association between leader humility and taking charge is significantly and positively, with organization-based self-esteem (OBSE) mediating the connection. We also found support for the moderating effect of leader prototypicality. Leader humility positively affect taking charge via followers’ organizational-based self-esteem while only in cases of high leader prototypicality. Finally, we probe into the practical and theoretical implications of this research.